Tacrolimus-Eluting Suture Inhibits Neointimal Hyperplasia: An Experimental In Vivo Study in Rats - AK, KORAY; ÖZKAN YENAL, NAZİYE; ARSAN, SİNAN (W B SAUNDERS CO LTD, 2017)
Objective/Background: Neointimal hyperplasia (NIH) remains one of the leading causes of graft failure after vascular anastomoses. Cytotoxic drugs, such as rapamycin and tacrolimus, have been shown to inhibit the development of NIH. In this study, the aim was to test the impact of a sustained releasing tacrolimus-chitosan-eluting suture on the development of NIH in a rat model. Methods: After tacrolimus-chitosan coating of a 7/0 polyvinylidene difluoride (PVDF) Trofilen (R) suture, the tacrolimus concentration on the coated suture and in vitro release trials were performed spectrophotometrically. Twelve Wistar rats were included. After midline laparotomy, a 7-8 mm longitudinal aortotomy in the infrarenal aorta was made and then closed by a bare 7/0 PVDF (group C, n = 6) and a 7/0 tacrolimus-chitosan coated PVDF suture (0.65 mu g/cm tacrolimus [0.9 wt%] + 1.82 mu/cm chitosan [2.28 wt%]) (group T, n = 6). After 1 month, rats were sacrificed and aortotomy sites were examined histologically by ratio of intimal area (including neointima) and immunohistochemically by alpha-smooth muscle actin (ASMA) and proliferating cell nuclear antigen (PCNA) immunostaining. The PCNA positive cells were indexed to total cell number and expressed as percentage. Results: In vitro tacrolimus release tests for a 7/0 tacrolimus-chitosan coated PVDF suture were confirmed for 1 month without an initial burst release. Endothelialisation over the aortotomy line occurred in both groups. The area of neointima was significantly reduced in group T compared with group C (ratio 0.22 +/- 0.12 vs. 0.42 +/- 0.11; p =.017) 1 month post-operatively. Likewise, the percentage of PCNA immunostaining significantly decreased in group C compared with group T (3.83 +/- 2.85% vs. 11.17 +/- 7.78%; p =.026). The cells constituting NIH were positive for ASMA immunostaining. Conclusions: Tacrolimus-chitosan-eluting suture is shown to be an effective way to reduce NIH without interfering with normal endothelialisation. (C) 2016 European Society for Vascular Surgery. Published by Elsevier Ltd. All rights reserved.
Keywords: Eluting suture; Endothelialisation and anastomosis; Neointimal hyperplasia; Tacrolimus-chitosan; DRUG-DELIVERY; ANASTOMOTIC STRICTURE; INTIMAL HYPERPLASIA; GENE-TRANSFER; CANINE MODEL; PREVENTION; RESTENOSIS; GRAFTS; INJURY